Groundwater Recharge Estimation Using Hydrus 1d Model in Alaşehir Sub-Basin of Gediz Basin in Turkey - Tonkul, Serhat; Baba, Alper; Tonkul, Serhat; Şimşek, Celalettin; Durukan, Seda; Demirkesen, Ali Can; Demirkesen, Ali Can; Tayfur, Gökmen; Tayfur, Gökmen; Baba, Alper (Springer Verlag, 2019)
Gediz Basin, located in the western part of Turkey constituting 2% land of the country, has an important groundwater potential in the area. Alasehir sub-basin, located in the southeast of the Gediz Basin and subject to the extensive withdrawal for the irrigation, constitutes the study area. Natural recharge to the sub-basin due to precipitation is numerically investigated in this study. For this purpose, 25 research wells, whose depths range from 20 to 50 m, were drilled to observe the recharge and collect the necessary field data for the numerical model. Meteorological data were collected from 3 weather stations installed in the study area. The numerical model HYDRUS was calibrated using the field water content data. Soil characterization was done on the core samples; the aquifer characterization was performed, and the alluvial aquifer recharge due to precipitation was calculated. As a result, the computed recharge value ranges from 21.78 to 68.52 mm, with an average value of 43.09 mm. According to the numerical model, this amount of recharge corresponds to 10% of the amount of annual rainfall.
Keywords: Alaşehir sub-basin; Aquifer recharge; Gediz Basin; Model calibration and validation; Numerical modeling; Precipitation